Rancangan kolam tanah dan aplikasi pompa serta filter air di Kelurahan Rumbai Bukit - Saberina Hasibuan; Novreta Ersyi Darfia; Rahmat Imam Mainil (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
An earthen pond was built at the location of catfish farming in Rumbai Bukit Village. Water sources come from springs, rainwater and water flow from surrounding channels. The volume of pond water during the dry season continuously decreases. The water level is reduced by > 10% per day in ponds 1, 2, and 3. To overcome the pond water level lowering, a pump is needed to drain water from pond 3 to pond 1 at the filter pond with a power of 16.23 watts. With the power requirements and pump capacity, the Aqua 125 W Pump was chosen, with a capacity of 30 Lpm, with a total head of 37 meters. Measurement of water quality before installing the pump and water filter showed that the pH ranged from 6.5-7.4, TDS ranged from 68-78 ppm, and the temperature was 27-34⁰C and after the pump and water filter were installed it was seen that the pH ranged from 6.6-7, 8 (an increase), TDS ranged from 66-41 ppm and a temperature of 26-29⁰C (decreased). The results obtained indicate that the application of pumps and water filters facilitates water circulation in ponds 1, 2, and 3 as well as 4, 5. Extension activities on the design of the soil pond and the application of pumps and water filters have overcome the decline in pond water levels during the dry season.